Bahasa Indonesia: english - Putri, Wahyuni Eka; Winarto, Winarto; Rahma, Haliatur (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2020)
Anthracnose or leaf fall disease caused by Gloeosporium gloeosporioides is a pathogen that attacks cocoa plants during the nursery phase and production. This study aimed to obtain the best rhizobacteria, which can induce cocoa seeds resistance to anthracnose and increase seedling growth. The study was conducted in a greenhouse, Faculty of Agriculture, Universitas Andalas, in 2019, using a randomized block design with 32 treatments and three replications. The treatments were the different isolates, sourced from Guguak (GK1, GK2, GK3), Akabiluru (AK1, AK2), Lubuk Minturun (LM1, LM2), Tanjung Alai (TA1, TA2, Ta3, TA4, TA5, TA6, TA7, TA8 , TA9, TA10, TA11, TA12, TA13, TA14, TA15, TA16, TA17, TA18), Singkarak (SK1, SK2, SK3, SK4, SK6), and two controls. The results showed that AK2 isolates from Akabiluru could suppress the development of anthracnose and support the growth of cocoa seedlings. The application of AK2 isolates was able to extend the incubation period of G. gloeosporioides, reduce the incidence of disease and the rate of disease infection, and help increase the number of areas and leaf numbers.Keywords: Anthracnose, cocoa seedling, Gloeosporium gloeosporioides, plant induction, Rhizobacteria